Alcohol-related presentations to the Royal Perth Hospital Emergency Department: A prospective study - McLay, S.; MacDonald, E.; Fatovich, Daniel (Wiley-Blackwell Publishing Asia, 2017)
Objective: To quantify and describe alcohol-related presentations to our ED, as part of the binational Alcohol Harm in Emergency Departments study. Methods: A prospective observational study at Royal Perth Hospital of every patient attending ED for the 168-h period commencing 08.00 hours Monday 1 December 2014. Patient presentations were classified as alcohol-related (alcohol-positive) using predefined criteria. These patients were compared to alcohol-negative patients on a range of demographic and clinical descriptors. Results: Two hundred and thirteen (15.2%) of 1403 patients screened were alcohol-positive. Compared with alcohol-negative patients, alcohol-positive patients were more likely to be male (148/213, 69.5% vs 636/1190, 53.4%, P < 0.001) and younger (mean 38 years vs 48 years, P < 0.001). They were more likely to arrive in police custody (OR 3.7, 95% CI 1.3–9.5, P = 0.005), and be admitted to the State Adult Major Trauma Unit (OR 4.2, 95% CI 2.1–8.3, P < 0.001). Forty-two (19.7%) of 213 patients had injuries suspected to be caused by an alcohol-affected third party. The ED length of stay and admission rate were not significantly different between the groups. Conclusions: 15.2% of patient presentations over the study week were alcohol-related. These patients were more likely to present with injury; one in five having injuries suspected to be caused by a third party affected by alcohol. This is a significant public health problem.